2007
DOI: 10.1039/b703361c
|View full text |Cite
|
Sign up to set email alerts
|

Increase in protoporphyrin IX after 5-aminolevulinic acid based photodynamic therapy is due to local re-synthesis

Abstract: Protoporphyrin IX (PpIX) fluorescence that is bleached during aminolevulinic acid (ALA) mediated photodynamic therapy (PDT) increases again in time after treatment. In the present study we investigated if this increase in PpIX fluorescence after illumination is the result of local re-synthesis or of systemic redistribution of PpIX. We studied the spatial distribution of PpIX after PDT with and without cooling using the skin-fold observation chamber model. We were unable to show a correlation between the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…In addition to affording a better treatment response profile, this PDT design also increases the feasibility of deep tissue PDT because it may allow for continuous accumulation of PSs at the treatment site, i.e., the first series of irradiation of PpIX in ALA-based PDT will lead to photobleaching of the PpIX and the time gap between irradiations will allow for resynthesis of PpIX to occur at the treatment site. The amount of PpIX reaccumulated at the treated site is demonstrated to be a function of the fluence rate of the first PDT dose 23, 41. These studies indicate that clever PS delivery strategies together with appropriate light illumination strategies could lend themselves to more efficacious deep tissue PDT.…”
Section: Light Delivery Strategies For Deep Tissue Pdtmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition to affording a better treatment response profile, this PDT design also increases the feasibility of deep tissue PDT because it may allow for continuous accumulation of PSs at the treatment site, i.e., the first series of irradiation of PpIX in ALA-based PDT will lead to photobleaching of the PpIX and the time gap between irradiations will allow for resynthesis of PpIX to occur at the treatment site. The amount of PpIX reaccumulated at the treated site is demonstrated to be a function of the fluence rate of the first PDT dose 23, 41. These studies indicate that clever PS delivery strategies together with appropriate light illumination strategies could lend themselves to more efficacious deep tissue PDT.…”
Section: Light Delivery Strategies For Deep Tissue Pdtmentioning
confidence: 86%
“…Allow the tissue to re-oxygenate, making subsequent irradiations effective and 2. Allow re-accumulation of photosensitizer at the lesion 23. While a few studies have shown that the necrotic depth induced by CW lasers is similar to thaFt seen with pulsed lasers, other studies have shown significant enhFancement in the necrotic depth resulting from pulsed irradiation 24-29.…”
Section: Light Delivery Strategies For Deep Tissue Pdtmentioning
confidence: 96%
“…When applied topically, ALA (but not its esters) is known to reach blood vessels 20, 21. Theoretically, ALA could be able to diffuse through the endothelium cell or maybe endothelial cells would be capable to synthesize porphyrins 36. Another factor is PDT drug distribution to vessels via intravascular delivery and often, lipoprotein receptor‐mediated uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This has important consequences for the general interpretation of fluorescence measurements in the window chamber. For example, in a previous study, our group determined the spatial distribution of the kinetics of protoporphyrin IX (PpIX) fluorescence during ALA-PDT [11]. PpIX fluorescence kinetics were measured in different tissue types and conclusions were based on data that was not corrected for differences in tissue optical properties and differences in the thickness within and between window chambers.…”
Section: Discussionmentioning
confidence: 99%